2011
DOI: 10.1158/1078-0432.ccr-10-2158
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment EGFR T790M Mutation and BRCA1 mRNA Expression in Erlotinib-Treated Advanced Non–Small-Cell Lung Cancer Patients with EGFR Mutations

Abstract: Purpose: Advanced non-small-cell lung cancer (NSCLC) patients harboring epidermal growth factor receptor (EGFR) mutations (deletion in exon 19 or L858R) show an impressive progression-free survival of 14 months when treated with erlotinib. However, the presence of EGFR mutations can only imperfectly predict outcome. We hypothesized that progression-free survival could be influenced both by the pretreatment EGFR T790M mutation and by components of DNA repair pathways.Experimental Design: We assessed the T790M m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
235
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(253 citation statements)
references
References 45 publications
13
235
4
1
Order By: Relevance
“…an area greater than 2.2 mm 2 were macrodissected; the rest of the samples were microdissected as previously described (21). In both cases, cells were dissected directly into 30 mL of PCR buffer (Ecogen) plus proteinase K (40 mg/mL) and incubated overnight at 60 C. Proteinase was inactivated by incubation at 100 C for 10 minutes and the resulting cell extract used for mutational analyses.…”
Section: Translational Relevancementioning
confidence: 99%
“…an area greater than 2.2 mm 2 were macrodissected; the rest of the samples were microdissected as previously described (21). In both cases, cells were dissected directly into 30 mL of PCR buffer (Ecogen) plus proteinase K (40 mg/mL) and incubated overnight at 60 C. Proteinase was inactivated by incubation at 100 C for 10 minutes and the resulting cell extract used for mutational analyses.…”
Section: Translational Relevancementioning
confidence: 99%
“…Rosell et al revealed that 80 of 129 patients with advanced NSCLC harboring EGFR mutations had responded to erlotinib (ORR is 68.9) in their cohort study [16]. In EURTAC, which was performed in a first-line setting, ORR was reported as 64% [5].…”
Section: Motoshima Et Al Page 13mentioning
confidence: 99%
“…Unfortunately, around 60% of these patients develop resistance to anti-EGFR treatment through a missense point mutation resulting in an amino-acid change from threonine to methionine in exon 20 of EGFR (EGFR T790M) (7)(8)(9)(10)(11)(12). This mutation is thought to not only appear during treatment, but in rare cases (<5%) can also be found in primary tumors not previously treated with TKIs (5,7,(13)(14)(15)(16). Detecting the T790M mutation is therefore of critical importance in guiding the treatment of NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%